PHYSICAL EDUCATION: CONTRIBUTING TO THE PERFORMANCE OF PHYSICAL SCHOOL (Fiep Bulletin - online, 2014)
Nowadays there are few existing opportunities for physical activity, as it increasingly shows the importance of physical education teacher in order to guide their students to become physically active thus reducing the risk of disease. Thus the aim of this work was to verify the influence of a motor intervention on physical performance of schoolchildren. Therefore we evaluated the physical performance of 40 students aged between 9 and 10 years through analysis of health indicators related to physical fitness Sport Project proposed by Brazil, the test were: body composition, flexibility, abdominal strength, lower limb strength and superior agility and speed. The evaluation was performed before and after application of 24 physical education classes. The results indicated that physical education classes were beneficial to students especially in the increasing flexibility, abdominal strength and agility. We also investigated the moments where the subjects perform physical activity and found that the school is the only time where subjects have physical education activities, evidencing the importance of planning for physical education programs that seek health development.
Keywords: Physical Fitness; High School; physical performance